Health and well-being of recently active U.S. scuba divers: potential implications for life expectancy - Buzzacott, Peter; Edelson, Charlie; Tillmans, Frauke; Chimiak, James (Undersea and Hyperbaric Medical Society, 2021)
Introduction/Background Health care, income, education, mental health and housing have not been described for active scuba divers. This study characterizes the demography, health and well-being of active adult U.S. scuba divers, compared with matched U.S. adults active in other pursuits. Materials and Methods The Behavioral Risk Factor Surveillance System (BRFSS) is a proportionally representative annual survey of adults in the U.S. Scuba diving was included in 2011-2019 surveys. A comparison group of three per diver was physically active (in activities other than diving) and matched on survey year, age, sex, and state of residence. Results reported in this study are national estimates. Results The dataset comprised 2,307,980 telephone survey responses, yielding an estimated 103,686,087 personyears of data, including 14,360 person-years of scuba diving data. Diving in Florida and California was 4,626 person-years (32%), weekly frequency one occasion/week, and median minutes/week were 120. In diving there were 137,266 males (80%) and 35,058 (20%) females. Adults aged 2': 65 years comprised 10% of the active divers. The table presents demography, personal circumstances and health status. Summary /Conclusion The picture these results paint is one in which it appears possible that active recreational scuba divers may enjoy additional anticipated life expectancy, though our results do not confirm (or even imply) this. The dive community awaits prospective birth cohort studies that include diving status, (or perhaps twin studies,in which one twin is a recreational scuba diver and the other is not), before we may even